Rights of a Muslim woman before and during marriage, and upon divorce as conferred by the Islamic Family Law (Federal Territories Act) 1984, Malaysia - Md Hashim, Noraini; Che Soh @ Yusoff, Roslina; , (2015)
Islam has put much emphasis on the rights of woman and they are evidently been laid down in Al Quran (the Holy Book) and As Sunnah (the tradition of the Prophet Muhammad). Similarly in Malaysia where Islam is the religion of the Federation, the rights of Muslim woman are protected by virtue of Islamic Family Law Act and Enactments of each state. These Act and Enactments are the combination of the four school of thoughts’ opinions but majority of the provisions are based on the Shafie school of thoughts as adopted by the Malay Muslims. However, the rights of a woman can only be protected by the law subjected to the conditions that her marriage is valid and registered. The rights start with the entitlement to the gifts exchanged in the case if there is breach of engagement, followed by the rights during marriage namely to have dower, marriage gift and maintenance. Next will be the rights upon divorce i.e. deferred dower and marriage gift, accommodation, maintenance during period of reconciliation, consolatory gift and matrimonial property. This article is qualitative in nature. Besides referring to Al Quran and As Sunnah, reference will also be made to the Islamic Family Law (Federal Territories Act), Malaysia, referred journal, articles and decided and undecided cases. It is hope that this article will shed some light on the rights of Muslim woman in the context of before and during marriage and upon divorce as practise in Malaysia.